PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) BERBANTUAN MEDIA PUZZLE UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS III SDN 02 MOJOREJO KOTA MADIUN - Mardiyatul Muna; Ivayuni Listiani; Sayekti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study is based on the problem of students' low proficiency in understanding material on fractions and learning outcomes in Mathematics lessons. Apart from that, the finding is that teachers dominate the class more than students when learning Mathematics using conventional techniques. As a result, students feel bored participating in class activities because the process is still repetitive. The aim of using the Student Teams Achievement Division (STAD) model supported by puzzle media is to create a collaborative and interactive learning environment that facilitates better conceptual understanding of fraction material and improves student learning outcomes. This type of research is classroom action research with research subjects of 29 class III students at SDN 02 Mojorejo. Based on the results of observations, there was an increase in each cycle, with a KKM of 70. In cycle I the average student learning outcome reached 70 with a completion percentage of 52%. Meanwhile, in cycle II the average student learning outcome reached 80 with a completion percentage of 86 %. So, based on the analysis of research results, it can be concluded that the application of the STAD type cooperative learning model assisted by puzzle media in class III students at SD Negeri 02 Mojorejo can improve mathematics learning outcomes.